Examining Perceptions of Rapid Population Growth in North and South Gondar Zones, Northwest Ethiopia - Alene, Getu Degu; Worku, Alemayehu (Journal of Health, Population and Nutrition, 2010)
Ethiopia is one of the most populous countries in Africa and ranks second only to Nigeria. Rapid population growth has hampered the country's development, making the eradication of extreme poverty and hunger difficult. This study which had two components-quantitative and qualitative-was aimed at exploring the perceptions of women and other social groups on the prevailing population pressures. The quantitative study involved 3,512 women aged 15-49 years. The qualitative study consisted of five focus-group discussions and six key-informant interviews. Over 90% of women (n=3,512) who participated in the quantitative study and nearly all the focus-group discussants and interviewees (n=39) felt that something should be done to keep the population from growing too fast. Most (over 90%) participants approved of the Government passing a law regarding the maximum number of children that a couple should have. It is, therefore, timely for the responsible bodies to exert maximum effort and commitment in responding to the emerging attitudes of the people by making the population problem a priority. Key words: Cross-sectional studies; Perceptions; Population growth; Ethiopia DOI: 10.3329/jhpn.v27i6.4330 J Health Popul Nutr 2009 Dec; 27(6): 784-793